2021
DOI: 10.1016/j.jadohealth.2020.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' Perceived Socio-Emotional Impact of COVID-19 and Implications for Mental Health: Results From a U.S.-Based Mixed-Methods Study

Abstract: Purpose COVID-19 has disrupted many aspects of adolescents' lives, yet little data are available that document their subjective experiences of the pandemic. In a mixed-methods study of U.S. adolescents, we examined (1) adolescents' perceptions of how their social and emotional lives had changed during COVID-19; and (2) associations between these perceived changes and indices of their mental health, above and beyond their prepandemic mental health status. Methods Four hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
284
3
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(376 citation statements)
references
References 26 publications
33
284
3
12
Order By: Relevance
“…Youth who perceived worsened mood and increased anxiety reported feeling less close to friends and family [24]. This suggests that strong social relationships might be a protective factor during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Youth who perceived worsened mood and increased anxiety reported feeling less close to friends and family [24]. This suggests that strong social relationships might be a protective factor during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Challenges related to studying were mentioned most frequently, including difficulty to stay motived, productive and manage one's time; followed by challenges with mental and physical health. Another study compared students' mental health measures before and during the pandemic (n=406, age M=15,24) using valid inventories for assessment of depression symptoms, affect, as well as other measures, and it was found that both anxiety, loneliness and depression symptoms show small, but statistically significant increase (Rogers, Ha & Ockey, 2021). Also, this study reported changes in students' relationship dynamics with friends and family, indicating challenges in their socio-emotional functioning.…”
Section: Research On Students' Skills and Attitudes During The Covid-19 Related Distance Learningmentioning
confidence: 81%
“…The Flynn effect, that of constant increase of IQ by decades with at least 3 points, has recently registered a dramatic decrease [9] but probably not yet evidenced by the compensating Dunning-Krueger phenomenon. A better resilience seems to be in the case of families, peers, teachers' involvement [8,10], and a balance between intellectual and physical tasks [8].…”
Section: International Challenges Of Psychiatric Care During the Covid-19 Pandemicmentioning
confidence: 99%